Metagenomic Next-Generation Sequencing for Pathogenic Diagnosis and Antibiotic Management of Severe Community-Acquired Pneumonia in Immunocompromised Adults - Sun, Ting; Wu, Xiaojing; Cai, Ying; Zhai, Tianshu; Huang, Linna; Zhang, Yi; Zhan, Qingyuan (Frontiers in Cellular and Infection Microbiology, 2021)
Background Metagenomic next-generation sequencing (mNGS) is a promising technique for pathogens diagnosis. However, application of mNGS in immunocompromised adults with severe community-acquired pneumonia (SCAP) is relatively limited. Methods We retrospectively reviewed 23 immunocompromised and 21 immunocompetent SCAP patients with mNGS detection from April 2019 to December 2019. The performances of pathogenic diagnosis and subsequently antibiotic adjustment in immunocompromised SCAP patients were compared to immunocompetent SCAP patients. The defined by days of therapy (DOT) method was used for estimate daily antibiotic use. Results There was a significant difference in the diagnostic positivity rate between mNGS and conventional test in both groups (P<0.001). Compared to immunocompetent patients, more mixed pathogens in immunocompromised patients were found (P=0.023). Before the availability of mNGS, the DOTs in immunocompromise patients were higher than immunocompetent patients (3.0 [3.0, 4.0] vs. 3.0 [2.0, 3.0], P=0.013). Compared to immunocompetent patients, immunocompromised patients had fewer full pathogen covered empirical antibiotic therapy (14.7% vs. 57.1%, P=0.022), more adjustments of antibiotic treatment (87.0%) vs. 57.1%, P=0.027). More than a half (13 of 23) SCAP patients in immunosuppressed group had reduced or downgraded antibiotic adjustments based on the results. Conclusions mNGS may be a useful technique for detecting mixed pathogens and personalized antibiotic treatment in immunocompromised SCAP patients.